Rhubarb Enema Decreases Circulating Trimethylamine N-Oxide Level and Improves Renal Fibrosis Accompanied With Gut Microbiota Change in Chronic Kidney Disease Rats - Ji, Chunlan; Li, Yin; Mo, Yenan; Lu, Zhaoyu; Lu, Fuhua; Lin, Qizhan; Liu, Xusheng; Zou, Chuan; Wu, Yuchi (Frontiers in Pharmacology, 2021)
Objectives: Trimethylamine N-oxide (TMAO), a metabolic product of gut flora, is increased in chronic kidney disease (CKD) subjects and is recognized as one type of uremic toxins which is associated with poor cardiovascular outcomes and kidney function loss. Previous studies have suggested that rhubarb enema could reduce circulating uremic toxins such as urea, creatinine, and indoxyl sulfate and also regulate the intestinal microbiota. However, whether rhubarb enema retards kidney dysfunction by reducing circulating TMAO and its underlying mechanism, are still unclear. The present study aims to investigate the impact of rhubarb enema on TMAO and its precursors, as well as on the intestinal microbiota in 5/6 nephrectomized (5/6Nx) CKD rats. Design: Rats in the treatment groups were given rhubarb enema after modeling. At the end of the study, blood, feces, and kidney tissues were collected and processed for biochemical analyses, histological and western blot analyses, 16S rRNA sequence and untargeted metabolomic analyses. Results: Rhubarb enema reduced serum TMAO and trimethylamine (TMA) levels, inhibited the expression of inflammatory markers (interleukin-6, tumor necrosis factor α and Interferon-γ) and alleviated tubular atrophy, monocyte infiltration and interstitial fibrosis in 5/6Nx CKD rats. Moreover, rhubarb enema significantly increased the abundance of some symbiotic bacteria and probiotics, while reduced the abundance of some potential pathogens at the genus level. In addition, Spearman’s correlation analysis revealed that lachnospiraceae and romboutsia were positively correlated with TMAO. Conclusion: Rhubarb enema decreases circulating TMAO level and improves renal fibrosis in 5/6Nx CKD rats, which may be related to the regulation of intestinal microbial community.